Transformasi Digital dalam Pelayanan Publik pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Aceh Tengah - Astinayanti, Astinayanti; Aisyah, Siti; Khairani, Cut (JPAP: Jurnal Penelitian Administrasi Publik, 2024)
The problem addressed in this research is the insufficient provision of supportive infrastructure for digital transformation. Similarly, the human resources aspect, both in terms of quantity and quality regarding the mastery of information technology, will impact the quality of services provided to the public. The research conducted at the Central Aceh Investment and Integrated One-Stop Service Office (DPMPTSP) has three objectives: 1) Analyzing the quality of service in digital transformation from the aspects of tangibles, reliability, responsiveness, assurance, and empathy. 2) Analyzing digital transformation in public services from the aspects of cataloging, transactions, horizontal, and vertical integration. 3) Analyzing obstacles and efforts made to accelerate digital transformation. The research method is qualitative, with informant selection through purposive sampling. The results show that public services, except for the tangibles aspect, are considered good in terms of reliability, responsiveness, assurance, and empathy. However, the facilities and infrastructure at DPMPTSP still need attention because most of them are inadequate for use in online licensing services. Furthermore, the digital transformation process, in terms of horizontal integration, has not been implemented at all, as local applications still stand alone and are not integrated with the Online Single Submission (OSS) application. Meanwhile, the obstacle encountered in implementing digital transformation is the inadequate budget for the digital transformation process. Efforts to accelerate the digital transformation process include preparing resources proficient in technology, preparing facilities and infrastructure, and conducting public awareness campaigns.